Knowledge and Power in the Philosophies of Ḥamīd al-Dīn Kirmānī and Mullā Ṣadrā Shīrāzī - Meisami, Sayeh (Springer International Publishing, 2018)
This book is a comparative study of two major Shīʿī thinkers Ḥamīd al-Dīn Kirmānī from the Fatimid Egypt and Mullā Ṣadrā from the Safavid Iran, demonstrating the mutual empowerment of discourses on knowledge formation and religio-political authority in certain Ismaʿili and Twelver contexts. The book investigates concepts, narratives, and arguments that have contributed to the generation and development of the discourse on the absolute authority of the imam and his representatives. To demonstrate this, key passages from primary texts in Arabic and Persian are translated and closely analyzed to highlight the synthesis of philosophical, Sufi, theological, and scriptural discourses. The book also discusses the discursive influence of Naṣīr al-Dīn Ṭūsī as a key to the transmission of Ismaʿili narratives of knowledge and authority to later Shīʿī philosophy and its continuation to modern and contemporary times particularly in the narrative of the guardianship of the jurist in the Islamic Republic of Iran.